'I Guess A Lot of People See Me as a Big Sister or a Friend': the role of intimacy in the celebrification of beauty vloggers. Issue 3 (4th May 2017) - Berryman, Rachel; Kavka, Misha
Abstract: With an impressive 11 million subscribers, Zoe 'Zoella' Sugg is among the most popular of the young adults who have recently obtained fame (and fortune) by posting videos to YouTube. She figures prominently in the beauty group, one of the fastest-growing and most overtly feminized subsets of the YouTube community, creating videos on lifestyle, fashion and beauty-related topics. However, to a greater extent than many of her peers, Sugg supports her product-oriented videos with vlogs that offer behind-the-scenes, intimate access to her life(style). In so doing, Zoe's videos encourage intimacy not simply between her viewers and the 'big sister' persona she adopts on-screen, but also between her audience and the commodities she associates herself with. This article argues that the success of the YouTube 'influencer' economy, both in terms of its gender predispositions and celebrity effects, depends on processes of commodification through intimacy, which Zoe Sugg mobilizes in exemplary fashion.